Lesions of the dorsomedial striatum delay spatial learning and render cue-based navigation inflexible in a water maze task in mice - Lee, Anni S.; André, Jessica M.; Pittenger, Christopher (Frontiers in Behavioral Neuroscience, 2014)
The dorsal striatum is involved in cue‐based navigation strategies and in the development of habits. It has been proposed that striatum‐dependent cued navigation competes with hippocampus‐dependent spatial navigation in some circumstances. We have previously shown that large lesions of the dorsal striatum, as well as impairment of corticostriatal synaptic plasticity in transgenic mice, can enhance spatial learning in a watermaze task, presumably by the disruption of competitive interference. However, the dorsal striatum is not a homogeneous structure; both anatomical considerations and experimental studies in various paradigms show that dorsomedial and dorsolateral striatum are functionally distinct, although there is no precise anatomical or neurochemical boundary between them. Here we investigated the effect of restricted excitotoxic lesions of dorsomedial striatum on cued and spatial water maze learning. We find that dorsomedial striatal lesions delay spatial learning but permit cued learning. After cued learning, lesioned animals showed inflexible search, resulting in repeated visits to the escape platform‐associated cue. These results support a role for the dorsomedial striatum in behavioral flexibility rather than in cued‐based navigation.